Efforts to Improve Student Learning Outcomes at SMP Negeri 4 Woyla Barat through Sharing and Audio Visual Media on the Material on Implementing Thaharah - Sufri, Asfu (Jurnal Profesi Guru Indonesia, 2025)
This study aimed to improve the learning outcomes of eighth-grade students in Islamic Religious Education (PAI) at SMP Negeri 4 Woyla Barat during the 2024/2025 academic year through the implementation of audiovisual learning media. Initial observations and pre-tests revealed that over 75% of the students had not yet achieved the Minimum Mastery Criteria (KKM), with an average daily test score of 68. Following the application of audiovisual media during two 45-minute learning cycles, there was a noticeable improvement in student learning outcomes. The percentage of students reaching mastery increased to 85%. This improvement indicates that the use of audiovisual learning media is effective in enhancing both students’ interest and academic achievement in PAI. The engaging nature of audiovisual content likely helped clarify complex concepts and maintained students’ attention throughout the lessons. These findings suggest that incorporating multimedia resources in religious education can be a valuable strategy for educators aiming to boost understanding and motivation among junior high school students. Consequently, it is recommended that schools consider integrating audiovisual media regularly in their teaching to support improved educational outcomes.